Efectos de la aplicación de ácidos húmicos en dos variedades del cultivo de fréjol phaseolus vulgaris l - Aguilar Marín, María Belén (2012)
In the St. Ines farm of the Technique University of Machala, it realized the consistent experiment in the fertilization of two varieties of bean, lines and butter with two sources of humus acid it approached the following goals: 1. To establish the action of humus acids in two varieties of bean (Phaseolus vulgaris L.) 2. To determinate the better treatment of fertilized and three. To carry out the economic analysis. The studied treatments in a design in blocks to random. During the development to crop it applied the humus acid twelve percent each fifteen days, using the manual bomb to sprinkling; while that, the humus acid seventy-five percent it applied directly to the ground / plant to the twenty days; it gave all the culture works, relatives to lose its leaves, and irrigation for gravity and fit sanitarian controls to control the effects of reticular fungus and plague of the foliage. The obtained results in the analysis of the different variables to threw high significance for all the analyzed variables to excepting for high of plant to the fifteen days. The varieties butter and lines, in the condition of fertility in the area of experiment answered to the organic fertilization with humus acids, potentiating the indexes of productivity; high of plant, weight of one-hundred fresh and dry grains, weight of one-hundred fresh and dry pey twit, number to pey twits for plant, size of the pey twits and profit of grain for hectare and plot. The production of pey twits, weight of grain for plot and hectare it superior in the variety lines plus humus acid twenty-one hectares and one-hundred ten kg/hectares with relation to the agriculture eyewitness of the butter variety the production of dry grain it appreciated in one-thousand two-hundred eighty-seven kg. hectares with variety lines plus two, cero one hectares of humus acid, recording to the variety butter and to the agriculture eyewitness. The absolute eyewitness of the variety butter and lines, in conditions of a poor ground in nitrogen and phosphorus and half in potassium, presenting indexes of productivity, in pey twits for plants, weight of one-hundred low seed and production of dry grain for hectare.